Preparticipation screening in young female elite ice hockey players - Mohl, Alexander; Pongratz, Janis; Muxel, Selina; Berger, Manuel; Berr, Michael; Schneider, Bastian; Schlichting-Knoob, Anna; Platz, Ulrich; Dorwarth, Uwe; Rogowski, Sebastian; Hoffmann, Ellen; Straube, Florian (Frontiers in Cardiovascular Medicine, 2024)
ObjectivesThe occurrence of sudden cardiac death (SCD) in competitive athletes has led to a discussion about appropriate preparticipation screening models. The role of an electrocardiogram (ECG) in routine testing remains controversial in current guidelines. Furthermore, data on cardiac findings and the prognostic utility of screening strategies in young female elite ice hockey is scarce.MethodsFemale elite ice hockey players were enrolled in the open prospective “General Evaluation Program for Arrhythmia-Related Death in Athletes” (GEPARD) registry from 2008 to 2018. A staged preparticipation screening was performed. The main goal was to determine the prevalence of SCD conditions and identify effective screening tools. The secondary aim was to study baseline results and follow-ups on a unique subgroup of young female ice hockey players.ResultsA total of 88 female ice hockey players, mean age 16 ± 1 years, were prospectively enrolled. The prevalence of conditions potentially leading to SCD during competition was 3.4% (3/88). The 12-lead ECG led to the diagnosis of one congenital long QT and one acute myocarditis and showed a number needed to screen of 44, with a specificity of 98%. One athlete demonstrated a relevant pericardial effusion on echocardiography, which was related to acute toxoplasmosis. No cases of SCD occurred during long-term follow-up.ConclusionThe subgroup of young female ice hockey players showed a notable prevalence of athletes “at risk” of 3.4%, which indicates the importance of preparticipation screening that features a 12-lead ECG as the most important component.